Achromatic metalens imaging for camera system - Tao, Rufei (Nanyang Technological University, 2021)
Metalens is one of the most advanced lens technology. Basing on the technique of metasurface, the metalens can realize a negative refraction, which can provide a larger bending angle as well as higher numerical aperture(NA) compared with traditional lens. In this dissertation, a novel design of metalens is established in Lumerical FDTD simulation, which is used to focus a mid-infrared band plane wave. In order to establish that metalens, a number of units which can bend the light with a particular angle are built, and the main task is finding the proper structure and size of those units to get a considerable efficiency. Then the performance of the metalens can be represented by analyzing the results from a line combination of those units.